Seawater desalination reverse osmosis membrane with antioxidant property and preparation method thereof

CN122937667APending Publication Date: 2026-10-20SHENZHEN XUHAI INVESTMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610901419.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本发明的目的在于克服现有技术存在的上述问题,提供一种具有抗氧化性的海水淡化反渗透膜及其制备方法,以解决现有海水淡化反渗透膜在氧化性运行或清洗环境下选择分离层易受氧化损伤,进而导致分离性能稳定性下降的问题

Benefits of technology

(1)本发明采用无机氧化物纳米核与酚羟基-胺基有机包覆层构成抗氧化纳米组分,将无机氧化物的氧化还原缓冲作用、酚羟基的自由基捕获作用以及胺基的界面结合能力集中在同一纳米单元上,使聚酰胺选择分离层获得更稳定的抗氧化保护。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1779760925465-000004
    Figure REF-OBJ-1779760925465-000004
  • Figure REF-OBJ-1779760925465-000005
    Figure REF-OBJ-1779760925465-000005
  • Figure REF-OBJ-1779760925465-000006
    Figure REF-OBJ-1779760925465-000006
Patent Text Reader

Abstract

This invention discloses an antioxidant seawater desalination reverse osmosis membrane and its preparation method. The reverse osmosis membrane comprises a porous support layer and a selective separation layer formed on its surface. The selective separation layer includes a polyamide separation matrix and antioxidant nano-components dispersed therein. The antioxidant nano-components consist of inorganic oxide nanocores and a phenolic hydroxyl-amine organic coating layer, and are enriched in the outer surface and near-surface regions of the selective separation layer. During preparation, an asymmetric porous support layer is formed through two-stage coagulation, followed by aqueous pre-wetting and two-stage organic phase interfacial polymerization to form the antioxidant selective separation layer. This invention improves the membrane's salt rejection rate retention and operational stability under oxidizing environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of membrane separation materials, and in particular to a seawater desalination reverse osmosis membrane with antioxidant properties and its preparation method. Background Technology

[0002] Seawater desalination is one of the important technological approaches to alleviate the shortage of freshwater resources in coastal areas. Reverse osmosis membrane technology, due to its high separation efficiency, relatively low operating energy consumption, and high system integration, has become the most widely used membrane separation technology in seawater desalination projects. Reverse osmosis membranes typically rely on a dense selective separation layer to achieve the selective transfer of water molecules and salt ions, and a porous support layer to provide mechanical support and permeable channels. Therefore, the stability of the membrane material's separation layer, the structural stability of the support layer, and its ability to maintain flux during long-term operation directly affect the operational reliability of the seawater desalination system.

[0003] In actual seawater desalination processes, the feed water typically contains microorganisms, organic matter, colloidal particles, and inorganic salt impurities. Membrane systems may also come into contact with chlorine-containing oxidants, peroxides, or other oxidizing chemicals during pretreatment, cleaning, or antibacterial processes. For common polyamide reverse osmosis membranes, the polyamide selective separation layer is prone to chemical structural damage under long-term oxidizing environments, leading to changes in membrane surface morphology, decreased salt rejection performance, and increased flux fluctuations. Furthermore, simply introducing inorganic fillers or antioxidants to improve the membrane's oxidation resistance may introduce new problems such as uneven dispersion, localized agglomeration, increased defects in the separation layer, and blockage of the support layer pores, making it difficult to achieve a balance between oxidation resistance, permeability, and salt rejection performance.

[0004] Therefore, the core technical problem that still needs to be solved for existing seawater desalination reverse osmosis membranes is how to improve the oxidation resistance of membrane materials while maintaining the integrity of the selective separation layer and the effective water permeability structure of the porous support layer, so that the reverse osmosis membrane can still have relatively stable separation performance under oxidizing operation or cleaning environment. Summary of the Invention

[0005] The purpose of this invention is to overcome the above-mentioned problems existing in the prior art and provide an antioxidant seawater desalination reverse osmosis membrane and its preparation method, so as to solve the problem that the selective separation layer of the existing seawater desalination reverse osmosis membrane is easily damaged by oxidation in oxidizing operation or cleaning environment, which leads to a decrease in the stability of separation performance.

[0006] To achieve the above objectives, the first aspect of the present invention provides a seawater desalination reverse osmosis membrane with antioxidant properties, comprising a porous support layer and a selective separation layer formed on one side surface of the porous support layer. The selective separation layer includes a polyamide separation matrix and antioxidant nanocomponents dispersed in the polyamide separation matrix. The antioxidant nanocomponents include inorganic oxide nanocores and phenolic hydroxyl-amine organic coating layers coated on the surface of the inorganic oxide nanocores. The antioxidant nanoparticles are distributed in the outer surface region and near-surface region of the selective separation layer. The outer surface region and near-surface region are areas that start from the outer surface of the selective separation layer and occupy 60% of the thickness of the selective separation layer. The amount of antioxidant nanoparticles in this region accounts for 65% to 90% of the total amount of antioxidant nanoparticles in the selective separation layer. The outer surface of the selective separation layer is covered with a continuously covered nanoparticle-like rough structure, which is composed of multiple adjacent spherical or near-spherical protrusions, with an average particle size of 30 nm to 180 nm. The porous support layer has an asymmetric pore structure, and along the direction away from the selective separation layer, it sequentially includes a dense transition region close to the selective separation layer, a finger-shaped pore region located below the dense transition region, and a sponge-like pore region located below the finger-shaped pore region. The thickness of the dense transition region is 0.3 μm to 3.0 μm, and fine pores with a diameter of less than 0.5 μm are distributed within the dense transition region.

[0007] Through the above structural design, the antioxidant nanocomponents are not simply randomly filled in the polyamide separation matrix, but are concentrated in the outer surface and near-surface regions where they are more easily exposed to oxidizing media. This allows oxidizing substances to contact the antioxidant nanocomponents in the initial stages of entering the polyamide separation matrix. The phenolic hydroxyl structure provides hydrogen donors and free radical trapping sites, the inorganic oxide nanonuclei participate in redox buffering, and the amine coating structure enhances the interfacial bonding between the nanocomponents and the polyamide network, concentrating the antioxidant effect on the most critically protected areas of the separation layer. This distribution also avoids the blockage of water transport paths caused by a large number of nanocomponents penetrating deep into the selective separation layer or entering the porous support layer, achieving a better balance between antioxidant protection, water flux, and salt retention performance. The rough, nanoparticle-like structure on the outer surface, composed of continuous adjacent spherical or near-spherical protrusions, increases the effective contact area without forming through-hole defects, while providing more accessible microscale interfaces for water molecules during surface wetting and mass transfer. The dense transition zone, finger-shaped pore zone, and sponge-like pore zone in the porous support layer work together in sequence to provide a smooth and continuous bearing interface for the selective separation layer, while maintaining water permeability channels through the finger-shaped pores and sponge-like pores below. This reduces the risk of local collapse, cracking, or downward migration of nano-components in the selective separation layer from the perspective of the overall membrane structure.

[0008] Preferably, the inorganic oxide nanonucleus is selected from cerium dioxide nanoparticles, manganese dioxide nanoparticles, zinc oxide nanoparticles, and titanium dioxide nanoparticles; the phenolic hydroxyl-amine organic coating layer is formed by a phenolic hydroxyl-containing compound and an amine-containing compound, wherein the phenolic hydroxyl-containing compound is selected from gallic acid, tannic acid, and dopamine, and the amine-containing compound is selected from m-phenylenediamine, polyethyleneimine, and triethylenetetramine.

[0009] Inorganic oxide nanonuclei provide a stable inorganic antioxidant framework, phenolic hydroxyl compounds provide active sites that can react with oxidative free radicals or reactive chlorine substances, and amine-containing compounds improve the compatibility and interfacial fixation between the coating layer and the polyamide separation matrix. The key here is not just the selection of antioxidant materials, but the combination of inorganic oxide nanonuclei, phenolic hydroxyl structures, and amine structures into a surface-coated nanocomposition. This concentrates the antioxidant activity of the nanonuclei, the sacrificial trapping effect of the phenolic hydroxyl groups, and the interfacial intercalation effect of the amine groups onto a single nanoscale unit. Such a structure makes it easier for nanoparticles to remain on the outer surface and near-surface region of the selective separation layer during interfacial polymerization or film formation, reducing the problems of nanoparticle sedimentation, aggregation, or penetration into the support layer due to surface energy differences. In practical terms, when the membrane surface is subjected to an oxidizing environment, the coating layer can initially absorb some of the oxidation, while the inorganic oxide nanonuclei maintain a redox buffer for a longer period, thereby improving the antioxidant stability of the reverse osmosis membrane during long-term seawater desalination operation.

[0010] Preferably, the average particle size of the antioxidant nanocomponent is 5 nm to 80 nm, and the mass content of the antioxidant nanocomponent in the selective separation layer is 0.05% to 2.0%; in the outer surface of the selective separation layer, the number of antioxidant nanocomponent agglomerates with a diameter greater than 500 nm in any 10 μm × 10 μm observation area does not exceed 8.

[0011] Limiting the particle size and content of antioxidant nanocomponents to a narrow and practically controllable range helps to balance the number of antioxidant active sites and the integrity of the selective separation layer. When the particle size is too large, the nanocomponents are prone to forming localized stress points or non-selective defects in the polyamide separation matrix; when the particle size is too small, although the dispersibility is good, an excessively high surface coating ratio may reduce the effective antioxidant contribution of the inorganic oxide nanonuclei. Controlling the average particle size to 5 nm–80 nm allows the nanocomponents to maintain a sufficiently small embedding size within the separation layer thickness scale, while retaining effective particle entities that can be fixed by the surface coating layer. Controlling the mass content to 0.05%–2.0% provides continuous but not excessive antioxidant active sites, avoiding damage to the compactness of the polyamide network due to excessive addition. Further limiting the number of large-sized aggregates can constrain the dispersion state of the nanocomponents from the perspective of membrane surface morphology, allowing them to participate in antioxidant and interface regulation more often as single particles or small clusters, rather than becoming salt leakage or mechanically weak points as large aggregates.

[0012] Preferably, nanoscale recesses are formed between the spherical or near-spherical protrusions, and the width of the nanoscale recesses is 10 nm to 120 nm; the thickness of the selective separation layer is 80 nm to 500 nm; a continuous bonding interface is formed between the selective separation layer and the porous support layer; and the selective separation layer has no through cracks under a 2 μm scale electron microscope.

[0013] Spherical or near-spherical protrusions and nanoscale recessed gaps together constitute a continuous surface undulation structure. The function of this structure is not limited to increasing roughness; more importantly, it forms a relatively uniform nanoscale mass transfer interface on the outer surface of the separation layer. When the width of the recessed gaps is controlled between 10 nm and 120 nm, it can form micro-spaces for water molecule contact and diffusion, without being large enough to create obvious contaminant embedding trenches or local defects. Selecting a separation layer thickness of 80 nm to 500 nm allows the polyamide separation matrix to maintain necessary salt retention paths while avoiding a decrease in water flux due to an excessively thick separation layer. The continuous bonding interface and the absence of penetrating cracks further demonstrate that the surface nanoparticle-like rough structure is a morphology-controlled process based on a complete separation layer, rather than an unstable structure formed by cracking, peeling, or localized accumulation. After this treatment, the membrane surface has both active protection from antioxidant nanocomponents and selective separation capability provided by the continuous polyamide network, making the overall structure more suitable for long-term pressure-driven seawater desalination operations.

[0014] Preferably, the thickness of the finger-shaped pore region accounts for 35% to 80% of the total thickness of the porous support layer, the thickness of the dense transition region accounts for 1% to 10% of the total thickness of the porous support layer, and the sponge-like pore region includes irregular interconnected pores with a pore size of 0.2 μm to 5 μm.

[0015] The porous support layer does not simply provide mechanical support; rather, it performs different structural functions through varying thickness proportions of different pore regions. The dense transition zone, though relatively small in proportion, is located close to the selective separation layer. This provides a smoother, finer-pored film-forming interface for the polyamide separation matrix, stabilizing the reaction front during interfacial polymerization and limiting the migration of antioxidant nanocomponents into the deeper layers of the support layer. The finger-like pore regions, occupying a larger proportion of the thickness, provide rapid water permeation channels extending along the membrane thickness direction, reducing flow resistance within the support layer. The sponge-like pore regions, through irregular interconnected pores, provide bottom support and lateral connectivity, helping to disperse pressure loads and preventing localized collapse of the finger-like pore regions under operating pressure. With these three elements working together, the fine structure of the selective separation layer and the mass transfer structure of the support layer can collaborate more stably, enabling the reverse osmosis membrane to maintain its antioxidant surface structure while exhibiting good water flux retention and pressure resistance stability.

[0016] Preferably, the finger-shaped pore region includes a plurality of elongated pores extending along the film thickness direction, the length of the elongated pores being 5μm to 45μm and the width being 0.5μm to 6μm; adjacent elongated pores are separated by porous framework walls, the porous framework walls having interconnecting pores with a diameter of 0.05μm to 1.5μm distributed on the porous framework walls; the maximum depth of the antioxidant nanocomponent entering the porous support layer does not exceed 1.5 times the thickness of the dense transition region.

[0017] The elongated pores extend along the membrane thickness direction, providing a more direct longitudinal channel for permeate water. The interconnecting pores on the porous framework walls provide localized lateral connectivity, preventing water flow from entirely relying on a single pore path and mitigating the impact of localized blockage on overall flux. Controlling the length and width of the elongated pores within the aforementioned range balances flux and framework strength, preventing excessively narrow pores from increasing mass transfer resistance and excessively wide pores from weakening support for the selective separation layer. Further limiting the maximum depth of the antioxidant nanocomponents within the porous support layer is a crucial aspect of the entire structure. This limitation indicates that the antioxidant nanocomponents primarily serve the surface and near-surface protection of the selective separation layer, rather than entering the support layer in large quantities and forming ineffective filler. This preserves the pore openness of the support layer while concentrating antioxidant activity in the region where the oxidizing medium first acts. For seawater desalination reverse osmosis membranes, this "surface-enriched, depth-restricted" nanocomponent distribution directly addresses the improvement of the membrane surface's antioxidant stability while reducing unnecessary interference with water transport channels and the support layer's pore structure.

[0018] The second aspect of the present invention provides a method for preparing the antioxidant seawater desalination reverse osmosis membrane as described above, comprising the following steps: S1, Preparation of a porous support layer: The film-forming polymer, a dense transition modifier, a pore-forming agent and an organic solvent are mixed to obtain a support layer casting solution. The support layer casting solution is coated on the surface of the substrate. After air retention and two-stage coagulation treatment, a porous support layer with a dense transition region, a finger-like pore region and a sponge-like pore region is obtained. S2, Preparation of antioxidant nano-dispersion: Inorganic oxide nanoparticles, phenolic hydroxyl compounds and amine compounds are dispersed in water and treated under pH conditions of 7.5 to 9.5 to obtain an antioxidant nano-dispersion with a phenolic hydroxyl-amine organic coating layer on the surface; S3, Preparation of aqueous phase wetting solution: mix m-phenylenediamine, acid absorbent, surface wetting regulator and antioxidant nano-dispersion obtained in step S2 to obtain aqueous phase wetting solution; S4, the porous support layer obtained in step S1 is brought into contact with the aqueous wetting liquid obtained in step S3 to remove excess liquid from the surface of the porous support layer, thereby obtaining a pre-wetting support layer with surface-loaded antioxidant nano-components and m-phenylenediamine. S5, the pre-wetting support layer obtained in step S4 is brought into contact with the first organic phase reaction liquid and the second organic phase reaction liquid in sequence. After heat treatment and water washing, a seawater desalination reverse osmosis membrane with antioxidant properties is obtained. The mass concentration of pyromellitic chloride in the first organic phase reaction solution is lower than that in the second organic phase reaction solution.

[0019] Through the above preparation process, the pore structure of the porous support layer, the surface state of the antioxidant nanocomponents, and the formation process of the polyamide selective separation layer are continuously linked, rather than simply adding the nano-antioxidant material to a conventional interfacial polymerization system. In S1, air retention and two-stage solidification processes first form a dense transition zone on the surface of the support layer, and then finger-like and sponge-like pore regions below it, making it easier for the subsequent aqueous wetting liquid to remain in the fine pores and transition regions near the surface. In S2, a phenolic hydroxyl-amine organic coating layer is formed under weakly alkaline conditions, giving the inorganic oxide nanoparticles both antioxidant active sites and an amine interface compatible with the polyamide network. In S3 and S4, the antioxidant nanocomponents are then introduced together with m-phenylenediamine onto the surface of the support layer, ensuring that the nanocomponents are already in a position where the separation layer is about to form before interfacial polymerization. In S5, a low-concentration first organic phase reaction solution is first used for a mild pre-reaction, followed by a higher-concentration second organic phase reaction solution to continue building the polyamide network. This segmented reaction method reduces the possibility of high-concentration acyl chlorides rapidly locking up the surface from the outset, making it easier for antioxidant nanocomponents to be fixed in the outer and near-surface regions, while maintaining the continuity and integrity of the selective separation layer. Overall, this method links the pore formation of the support layer, nanocomponent coating, aqueous phase pre-positioning, and segmented polymerization of the organic phase into a process chain, which is beneficial for obtaining a reverse osmosis membrane structure with concentrated surface antioxidant activity, open support layer channels, and controlled defects in the separation layer.

[0020] Preferably, in step S1, the film-forming polymer is selected from polysulfone, polyethersulfone, and polyvinylidene fluoride; the dense transition modifier is selected from polyvinylpyrrolidone, polyethylene glycol, and sulfonated polyethersulfone; and the pore-forming agent is selected from polyethylene glycol, lithium chloride, and glycerol. In the casting solution of the support layer, the mass content of the film-forming polymer is 14%–22%, the mass content of the dense transition modifier is 0.3%–2.5%, the mass content of the pore-forming agent is 2%–10%, and the mass content of the organic solvent is 65.5%–83.7%. The air residence time is 8s to 35s; the two-stage coagulation process includes a first stage coagulation process and a second stage coagulation process. The first stage coagulation process uses an aqueous solution containing 5% to 20% organic solvent and the processing time is 10s to 80s. The second stage coagulation process uses water and the processing time is 5min to 30min.

[0021] The film-forming polymer provides the basic skeletal strength of the support layer, while the dense transition modifier mainly affects film shrinkage and pore formation near the surface, and the pore-forming agent regulates the solvent-to-non-solvent exchange rate during phase transformation. Crucially, air retention and two-stage coagulation are not simply routine treatments to improve pore structure; they are synergistic with the subsequent surface loading of antioxidant nanocomponents. Air retention time controlled between 8 and 35 seconds allows for moderate solvent evaporation and polymer enrichment on the casting solution surface, initially forming a denser surface environment. The first stage of coagulation uses an aqueous solution containing organic solvents, which slows down instantaneous phase separation, creating a moderately thick dense transition zone near the selectively separated layer. The second stage of coagulation uses water to fully complete the phase transformation, stabilizing the underlying finger-like and sponge-like pore regions. The resulting support layer surface is neither an overly open coarse pore nor a completely closed dense skin, but rather a transitional region with fine porosity, wettability, and load-bearing capacity. During subsequent aqueous phase wetting, m-phenylenediamine and antioxidant nano-components can remain near this transition region and are less likely to rapidly penetrate into the depths of the support layer, thus providing a more stable structural basis for the formation of the surface-enriched antioxidant separation layer.

[0022] Preferably, in step S2, the mass ratio of the inorganic oxide nanoparticles, the phenolic hydroxyl compound, and the amine compound is 1:0.05-0.40:0.03-0.30; In step S3, the aqueous phase wetting solution comprises the following components in the indicated mass percentages: m-phenylenediamine 1.5%–4.0%, acid absorbent 0.5%–3.0%, surface wetting modifier 0.005%–0.08%, antioxidant nano-components 0.005%–0.20%, and the balance being water; The acid absorbent is selected from one of triethylamine, camphor sulfonate, and sodium bicarbonate, and the surface wetting modifier is selected from one of sodium dodecyl sulfate, polyether-modified siloxane, and fatty alcohol polyoxyethylene ether.

[0023] The controlled ratio of inorganic oxide nanoparticles, phenolic hydroxyl compounds, and amine compounds ensures that the organic coating layer formed on the nanoparticle surface is neither too thin nor too thick. If the coating layer is too thin, the binding force between the nanoparticles and the polyamide system is insufficient, making them prone to migration or aggregation during aqueous wetting and organic phase contact. If the coating layer is too thick, it may obscure the effective antioxidant surface of the inorganic oxide nanocore, causing the nanoparticles to behave more as inert fillers. The aforementioned ratio allows phenolic hydroxyl and amine groups to be simultaneously distributed on the nanoparticle surface; the former acts as a free radical trap and oxidation buffer, while the latter enhances the interfacial intercalation with the reaction system of m-phenylenediamine and trimesoyl chloride.

[0024] The m-phenylenediamine, acid absorbent, surface wetting modifier, and antioxidant nanocomponents in the aqueous wetting solution collectively determine the reaction front of subsequent interfacial polymerization. The m-phenylenediamine concentration ensures the density of the polyamide network; the acid absorbent neutralizes acidic byproducts generated during the interfacial reaction, helping to maintain amine activity and reaction continuity; the surface wetting modifier improves the spreading of the aqueous phase on the porous support layer surface, preventing the antioxidant nanocomponents from localized accumulation; and the antioxidant nanocomponent content is controlled at 0.005%–0.20%, providing sufficient surface active sites while preventing excessive nanoparticle entry into the pores or disruption of the dense structure of the separation layer. This formulation does not simply aim to add more nanoparticles, but rather to allow the nanocomponents to undergo dispersion, localization, and reaction compatibility pretreatment in the aqueous phase, making it easier for the subsequently formed polyamide layer to simultaneously possess antioxidant properties and selective separation integrity.

[0025] Preferably, in step S5, the first organic phase reaction solution includes pyromellitic trimethylol chloride and an organic solvent with a mass concentration of 0.005% to 0.05%, and the contact time between the pre-wetting support layer and the first organic phase reaction solution is 3s to 20s. The second organic phase reaction solution includes 0.06% to 0.25% trimesoyl chloride and an organic solvent, and the contact time between the pre-wetted support layer and the second organic phase reaction solution is 15s to 90s. The heat treatment temperature is 50℃~90℃, and the time is 2min~10min; The mass concentration of pyromellitic chloride in the first organic phase reaction solution is 5% to 40% of the mass concentration of pyromellitic chloride in the second organic phase reaction solution.

[0026] By using different concentrations of trimesoyl chloride in the first and second organic phase reaction solutions, the interfacial polymerization process can be divided into two stages: surface pre-fixation and network densification. The first organic phase reaction solution has a lower concentration and shorter contact time, primarily forming an initial polyamide thin layer on the surface of the pre-wetted support layer and gently fixing the surface-loaded antioxidant nanocomponents. Due to the lower chloride concentration, the initial reaction does not form a highly cross-linked hard shell too quickly, allowing m-phenylenediamine and antioxidant nanocomponents to maintain a certain distribution adjustment space near the surface, which is beneficial for the formation of enriched states in both the outer and near-surface regions.

[0027] The second organic phase reaction solution has a higher concentration and a longer contact time, primarily used to further enhance the crosslinking density and selective separation capability of the polyamide network. After this treatment, the antioxidant nano-components already positioned in the previous stage are further embedded or encapsulated within the polyamide separation matrix, making them less prone to loss during washing and operation. Simultaneously, the polyamide network formed in the second stage can cover and connect the micro-regions generated in the initial reaction, ensuring the separation layer remains continuous without interconnected defects. The concentration of the first organic phase reaction solution is limited to 5%–40% of the second organic phase reaction solution concentration to reflect the gradient difference between the two reaction stages. If the proportion is too low, the first stage's fixation effect is insufficient; if the proportion is too high, the first stage is prone to over-reaction, causing the nano-components to be rapidly sealed on the surface or form localized accumulations. Combined with heat treatment at 50℃–90℃ for 2 min–10 min, the residual acyl chloride and amine groups can continue to react, stabilizing the interface between the polyamide network and the nano-components. In terms of overall effect, this segmented organic phase reaction method enables the surface positioning of antioxidant nanocomponents, the densification of polyamide networks, and the formation of nanoparticle morphology on the film surface to be achieved in a coordinated manner in the same preparation process.

[0028] The present invention, by adopting the above technical solution, has the following beneficial effects: (1) The present invention uses inorganic oxide nanocores and phenolic hydroxyl-amine organic coating layers to form antioxidant nanocomponents, which concentrate the redox buffering effect of inorganic oxides, the free radical capture effect of phenolic hydroxyl groups and the interfacial binding ability of amine groups on the same nanounit, so that the polyamide selective separation layer can obtain more stable antioxidant protection.

[0029] (2) The present invention makes the antioxidant nano-components mainly distributed in the outer surface region and near-surface region of the selective separation layer, and restricts their migration depth into the porous support layer, so that the antioxidant active sites are concentrated in the position of preferential contact with the oxidizing medium, while maintaining the openness of the support layer pores, thus taking into account both antioxidant and water permeability.

[0030] (3) By limiting the particle size, content and number of large-size agglomerates of the antioxidant nanocomponents, and forming a continuous nanoparticle-like rough structure on the outer surface of the selective separation layer, the present invention increases the effective contact area of ​​the surface while reducing the agglomeration of nanocomponents, non-selective defects and through cracks, which is beneficial to maintaining salt retention performance and film stability.

[0031] (4) The present invention forms an asymmetric porous support layer by means of a dense transition zone, a finger-shaped pore zone and a sponge-like pore zone, so that a fine-pore bearing interface is formed on the side near the selective separation layer, and a water-permeable channel and bottom connection support are maintained below along the film thickness direction, thereby improving the film formation stability of the selective separation layer and the structural reliability under pressure operation conditions.

[0032] (5) The present invention uses air retention, two-stage coagulation treatment, surface coating of antioxidant nano-components, water pre-wetting, and segmented interfacial polymerization of low-concentration first organic phase and high-concentration second organic phase to make the pore structure of the support layer, the surface positioning of nano-components and the densification process of polyamide network work together to simultaneously obtain the surface antioxidant enrichment structure, the complete selective separation layer and the stable water-permeable support structure. Attached Figure Description

[0033] Figure 1 This is a cross-sectional scanning electron microscope image of the seawater desalination reverse osmosis membrane obtained in Example 1.

[0034] Figure 2 The image shows a scanning electron microscope image of the outer surface of the selective separation layer of the seawater desalination reverse osmosis membrane obtained in Example 1. Detailed Implementation

[0035] The specific embodiments of the present invention will be described in detail below. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.

[0036] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.

[0037] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0038] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.

[0039] The present invention will now be described in detail with reference to specific embodiments, which are intended to understand rather than limit the invention.

[0040] Example 1

[0041] This embodiment discloses a seawater desalination reverse osmosis membrane with antioxidant properties, including a porous support layer and a selective separation layer formed on one side surface of the porous support layer. The selective separation layer includes a polyamide separation matrix and antioxidant nano-components dispersed in the polyamide separation matrix. The antioxidant nano-components include cerium dioxide nanonuclei and a gallic acid-polyethyleneimine organic coating layer coated on the surface of the cerium dioxide nanonuclei.

[0042] In this embodiment, the raw materials used to prepare the seawater desalination reverse osmosis membrane with antioxidant properties include porous support layer casting solution, antioxidant nano-dispersion solution, aqueous phase wetting solution, first organic phase reaction solution and second organic phase reaction solution, and the composition of each raw material is as follows.

[0043] The porous support layer casting solution comprises the following components by weight: 18.0 parts polysulfone, 1.2 parts polyvinylpyrrolidone, 4.0 parts lithium chloride, and 76.8 parts N,N-dimethylformamide.

[0044] Among them, the polysulfone is bisphenol A type polysulfone with a weight average molecular weight of 65,000 and a glass transition temperature of 185℃; the K value of polyvinylpyrrolidone is 30; the lithium chloride is anhydrous lithium chloride with a purity of 99.0%; and the purity of N,N-dimethylformamide is 99.5%.

[0045] The antioxidant nano-dispersion comprises the following components by weight: 1.00 parts cerium dioxide nanoparticles, 0.18 parts gallic acid, 0.12 parts polyethyleneimine, and 198.70 parts deionized water.

[0046] Among them, the cerium dioxide nanoparticles are cubic fluorite-type cerium dioxide nanoparticles with an original average particle size of 20 nm, a particle size distribution D90 of 45 nm, and a purity of 99.5%; the gallic acid is 3,4,5-trihydroxybenzoic acid with a purity of 99.0%; the polyethyleneimine is branched polyethyleneimine with a weight-average molecular weight of 1800, and primary, secondary, and tertiary amines are all present in the molecular structure; the conductivity of the deionized water is 0.8 μS / cm.

[0047] The aqueous wetting solution comprises the following components by weight: 2.5 parts m-phenylenediamine, 1.2 parts triethylamine, 0.025 parts sodium dodecyl sulfate, 7.69 parts antioxidant nano-dispersion, and 88.585 parts deionized water. The antioxidant nano-components constitute 0.05% of the aqueous wetting solution by mass.

[0048] Among them, the purity of m-phenylenediamine is 99.0%; the purity of triethylamine is 99.0%; and the purity of sodium dodecyl sulfate is 98.0%.

[0049] The first organic phase reaction solution comprises the following components by weight: 0.020 parts of trimesoyl chloride and 99.980 parts of n-hexane.

[0050] The second organic phase reaction solution comprises the following components by weight: 0.120 parts of trimesoyl chloride and 99.880 parts of n-hexane.

[0051] The purity of pyromellitic chloride is 98.0%; the purity of n-hexane is 99.0%; and the water content is not higher than 0.02 wt%. The mass concentration of pyromellitic chloride in the first organic phase reaction solution is 16.7% of the mass concentration of pyromellitic chloride in the second organic phase reaction solution.

[0052] The nonwoven fabric substrate is polyester nonwoven fabric with a thickness of 100μm and a basis weight of 80g / m². 2 .

[0053] Based on the above-mentioned raw material composition, this embodiment prepares a seawater desalination reverse osmosis membrane with antioxidant properties according to the following steps.

[0054] S1. Preparation of porous support layer 76.8 parts by weight of N,N-dimethylformamide were added to a dry reaction vessel equipped with mechanical stirring. 4.0 parts by weight of anhydrous lithium chloride were added at 25°C. The mixture was stirred at 300 rpm for 30 min to completely dissolve the anhydrous lithium chloride, thus obtaining the first mixture.

[0055] Add 1.2 parts by weight of polyvinylpyrrolidone to the first mixture and stir at 400 rpm for 40 min to uniformly disperse and dissolve the polyvinylpyrrolidone, thus obtaining the second mixture.

[0056] 18.0 parts by weight of polysulfone were added to the second mixture in four portions, with 4.5 parts by weight added each time. After each addition, the mixture was stirred at 500 rpm for 20 min. After all the polysulfone was added, the temperature was raised to 60°C and stirred at 500 rpm for 6 h to obtain a uniform and transparent support layer casting solution.

[0057] The support layer casting solution was allowed to stand at 60℃ for 4 hours to degas, and then cooled to 25℃. A polyester nonwoven fabric substrate was fixed to a glass plate, and the support layer casting solution was applied to the surface of the substrate using a doctor blade with a blade spacing of 180 μm and a coating speed of 8 cm / s. After coating, the substrate coated with the support layer casting solution was allowed to remain in air at 25℃ and 55% relative humidity for 18 seconds.

[0058] After the air residence period, the substrate coated with the support layer casting solution was immediately immersed in the first coagulation bath for 45 seconds. The first coagulation bath was an aqueous solution containing 10.0 wt% N,N-dimethylformamide at a temperature of 25°C. It was then transferred to the second coagulation bath for 15 minutes. The second coagulation bath was deionized water at a temperature of 25°C. After treatment, the membrane was soaked in fresh deionized water for 12 hours, with the deionized water changed every 3 hours, resulting in a porous support layer.

[0059] The cross-sectional structure of the seawater desalination reverse osmosis membrane obtained in this embodiment is as follows: Figure 1As shown in the figure. Combined with cross-sectional electron microscopy observation, the porous support layer exhibits an asymmetric pore structure. The side near the selective separation layer is a relatively dense transition region, the middle section contains finger-like pores extending along the film thickness direction, and the lower section is a sponge-like interconnected pore region. Image measurements and statistics indicate that the thickness of the dense transition region is approximately 1.2 μm, the finger-like pore region accounts for approximately 62% of the total thickness of the porous support layer, the average length of the elongated pores is approximately 26 μm, and the average width is approximately 2.8 μm. Figure 1 The porous support layer has a fine transition structure at the top, a finger-like pore structure extending along the film thickness direction in the middle, and a connected porous structure at the bottom.

[0060] S2. Preparation of antioxidant nanodispersion 198.70 parts by weight of deionized water were added to the reaction vessel, and 1.00 parts by weight of cerium dioxide nanoparticles were added at 25°C. The mixture was stirred at 600 rpm for 20 min, and then ultrasonically dispersed for 15 min at an ultrasonic power of 300 W. During the ultrasonic process, the temperature of the dispersion was controlled to not exceed 30°C to obtain a cerium dioxide initial dispersion.

[0061] 0.18 parts by weight of gallic acid were added to the initial cerium dioxide dispersion, and the mixture was stirred at 500 rpm for 20 min. Then, 0.12 parts by weight of branched polyethyleneimine were added, and the mixture was stirred at 500 rpm for another 20 min. The pH of the system was adjusted to 8.5 using a 0.1 mol / L sodium hydroxide aqueous solution, and the reaction was carried out at 25 °C with stirring at 500 rpm for 4 h. After the reaction was completed, the mixture was filtered through a 0.22 μm polyethersulfone membrane, and the filtrate was collected to obtain an antioxidant nano-dispersion with a gallic acid-polyethyleneimine organic coating on the surface.

[0062] In the obtained antioxidant nano-dispersion, the average particle size of the antioxidant nano-components is 38 nm, and the surface of the cerium dioxide nano-cores is coated with an organic coating layer containing phenolic hydroxyl groups and amine groups.

[0063] S3. Preparation of aqueous wetting solution Add 88.585 parts by weight of deionized water to a clean container, then add 2.5 parts by weight of m-phenylenediamine at 25°C and stir at 400 rpm for 20 minutes until the m-phenylenediamine is completely dissolved. Next, add 1.2 parts by weight of triethylamine and stir at 400 rpm for 10 minutes, then add 0.025 parts by weight of sodium dodecyl sulfate and stir at 400 rpm for 15 minutes. Finally, add 7.69 parts by weight of the antioxidant nano-dispersion obtained in step S2 and stir at 500 rpm for 30 minutes to obtain an aqueous wetting solution.

[0064] The obtained aqueous phase wetting solution showed no visible precipitate after standing for 10 minutes. It was stirred at 300 rpm for 5 minutes before use.

[0065] S4. Preparation of the pre-impregnated support layer The porous support layer obtained in step S1 is cut into a membrane sheet with a size of 20cm × 20cm, and the membrane sheet is fixed on a flat glass plate with the film-forming surface facing upwards. The aqueous phase wetting solution obtained in step S3 is poured onto the film-forming surface of the porous support layer so that the aqueous phase wetting solution completely covers the film surface, and the contact time is 120s.

[0066] After contact, the excess aqueous wetting liquid on the membrane surface is poured off, and a rubber roller is used to roll it twice in the same direction at a pressure of 0.02 MPa to remove excess liquid from the surface of the porous support layer, so that the membrane surface is kept uniformly wetted and free of obvious droplets, thus obtaining a pre-wetting support layer with surface loaded with antioxidant nano-components and m-phenylenediamine.

[0067] S5, Forming a selective separation layer The pre-wetted support layer obtained in step S4 is brought into contact with the first organic phase reaction solution for 10 seconds. After contact, the first organic phase reaction solution is immediately poured off, and the film surface is allowed to drain naturally for 15 seconds.

[0068] The membrane surface was then brought into contact with the second organic phase reaction solution for 45 seconds. After contact, the second organic phase reaction solution was poured off, and the membrane surface was allowed to drain naturally for 30 seconds.

[0069] The membrane that has completed the interfacial polymerization reaction was placed in a hot air drying oven for heat treatment at 70℃ for 5 minutes. After heat treatment, the membrane was washed in deionized water at 25℃ for 10 minutes, and then immersed in fresh deionized water for 30 minutes to obtain a seawater desalination reverse osmosis membrane with antioxidant properties.

[0070] In continuous fabrication, the porous support layer obtained in step S1 can be continuously drawn in roll form instead of being cut into sheets. The effective width of the porous support layer is 800 mm, the length of a single roll is 100 m, and the drawing speed is 1.0 m / min. The membrane material sequentially passes through an aqueous phase wetting tank, a liquid removal roller, a first organic phase reaction tank, a second organic phase reaction tank, a hot air treatment zone, and a water washing zone. The contact time in each zone is consistent with the corresponding steps in this embodiment. By adjusting the effective length of each treatment zone, the aqueous phase wetting time is 120 s, the first organic phase reaction time is 10 s, the second organic phase reaction time is 45 s, and the heat treatment time is 5 min.

[0071] The obtained seawater desalination reverse osmosis membrane comprises a porous support layer and a selective separation layer formed on one side of the porous support layer. The selective separation layer comprises a polyamide separation matrix and antioxidant nano-components dispersed in the polyamide separation matrix. The selective separation layer has a thickness of 210 nm, and a continuous bonding interface is formed between the selective separation layer and the porous support layer. No through cracks are observed in the selective separation layer under a 2 μm scale electron microscope.

[0072] Cross-sectional energy dispersive spectroscopy (EDS) and surface elemental distribution analysis revealed that the antioxidant nanoparticles were mainly distributed in the outer surface and near-surface regions of the selective separation layer. The outer surface and near-surface regions, defined as the area representing 60% of the selective separation layer's thickness, accounted for 78% of the total antioxidant nanoparticles in the selective separation layer. The maximum depth of the antioxidant nanoparticles penetrating the porous support layer was 1.4 μm, not exceeding 1.5 times the thickness of the dense transition zone.

[0073] The selected separation layer has a continuously covered, rough, nanoparticle-like structure on its outer surface. Statistical analysis of at least five different locations within a 10 μm × 10 μm electron microscopy observation area revealed the presence of 2, 3, 3, 4, and 3 aggregates of antioxidant nanoparticles with diameters greater than 500 nm, with an average of 3. The mass content of the antioxidant nanoparticles in the selected separation layer was 0.42%.

[0074] The cross-sectional structure of the seawater desalination reverse osmosis membrane obtained in this embodiment is as follows: Figure 1 As shown in the figure, cross-sectional electron microscopy reveals that the porous support layer exhibits an asymmetric pore structure. The side closest to the selective separation layer is a relatively dense transition region, the middle section consists of finger-like pores extending along the film thickness direction, and the lower section is a sponge-like interconnected pore region. Statistical measurements of images from at least five cross-sectional electron microscopy fields showed that the average thickness of the dense transition region was 1.2 μm, the finger-like pore region accounted for 62% of the total thickness of the porous support layer, the average length of the elongated pores was 26 μm, and the average width was 2.8 μm. This indicates that the porous support layer forms an asymmetric pore structure combining a dense upper support, a longitudinally permeable middle section, and a connected lower support.

[0075] Select the surface morphology of the separation layer, such as Figure 2 As shown, combined with surface electron microscopy observation, the outer surface of the selected separation layer exhibits a continuously covered nanoparticle-like rough structure. This nanoparticle-like rough structure consists of multiple adjacent spherical or near-spherical protrusions, without obvious through cracks or large-area delamination areas. Statistical analysis of images from at least five surface electron microscopy fields revealed that the average particle size of the spherical or near-spherical protrusions is 92 nm, with nanoscale recesses forming between adjacent protrusions, and an average width of 48 nm between these recesses. This indicates that the selected separation layer forms a nanoscale undulating surface while maintaining its continuous integrity.

[0076] Example 2

[0077] This embodiment discloses a seawater desalination reverse osmosis membrane with antioxidant properties. The difference from Example 1 is that the antioxidant nanocomponent is formed by manganese dioxide nanocores, tannic acid and triethylenetetramine. The mass concentration of trimesoyl chloride in the first organic phase reaction solution and the second organic phase reaction solution is adaptively adjusted. The composition of other raw materials and preparation steps are consistent with those in Example 1.

[0078] In this embodiment, the antioxidant nano-dispersion comprises the following components by weight: 1.00 parts manganese dioxide nanoparticles, 0.22 parts tannic acid, 0.10 parts triethylenetetramine, and 198.68 parts deionized water.

[0079] Among them, the manganese dioxide nanoparticles are mainly δ-type manganese dioxide nanoparticles with an original average particle size of 25nm, a particle size distribution D90 of 55nm, and a purity of 98.5%; the tannic acid purity is 98.0%; the triethylenetetramine purity is 98.0%; and the deionized water conductivity is 0.8μS / cm.

[0080] The aqueous phase wetting solution comprises the following components by weight: 2.8 parts m-phenylenediamine, 1.0 part triethylamine, 0.020 parts sodium dodecyl sulfate, 7.58 parts antioxidant nano-dispersion, and 88.60 parts deionized water. The antioxidant nano-components constitute 0.05% of the aqueous phase wetting solution by mass.

[0081] The first organic phase reaction solution comprises, by weight, the following components: 0.025 parts of pyromellitic methyl chloride and 99.975 parts of n-hexane.

[0082] The second organic phase reaction solution comprises the following components by weight: 0.140 parts of pyromellitic methyl chloride and 99.860 parts of n-hexane.

[0083] The purity of pyromellitic chloride is 98.0%; the purity of n-hexane is 99.0%; and the water content is not higher than 0.02 wt%. The mass concentration of pyromellitic chloride in the first organic phase reaction solution is 17.9% of the mass concentration of pyromellitic chloride in the second organic phase reaction solution.

[0084] In the preparation process, 198.68 parts by weight of deionized water were added to the reaction vessel in S2, and 1.00 parts by weight of manganese dioxide nanoparticles were added at 25°C. The mixture was stirred at 600 rpm for 20 min, followed by ultrasonic dispersion for 15 min at an ultrasonic power of 300 W. During the ultrasonic process, the temperature of the dispersion was controlled to not exceed 30°C to obtain a preliminary manganese dioxide dispersion. 0.22 parts by weight of tannic acid were added to the preliminary manganese dioxide dispersion, and the mixture was stirred at 500 rpm for 20 min. Then, 0.10 parts by weight of triethylenetetramine was added, and the mixture was stirred at 500 rpm for another 20 min. The pH of the system was adjusted to 8.8 using a 0.1 mol / L sodium hydroxide aqueous solution, and the mixture was stirred at 500 rpm for 4 h at 25°C. After the reaction was completed, the mixture was filtered through a 0.22 μm polyethersulfone membrane, and the filtrate was collected to obtain an antioxidant nano-dispersion with a tannic acid-triethylenetetramine organic coating on the surface.

[0085] In step S3, 88.60 parts by weight of deionized water were added to a clean container, and 2.8 parts by weight of m-phenylenediamine were added at 25°C. The mixture was stirred at 400 rpm for 20 min to completely dissolve the m-phenylenediamine. Then, 1.0 part by weight of triethylamine was added and stirred at 400 rpm for 10 min. Next, 0.020 parts by weight of sodium dodecyl sulfate was added and stirred at 400 rpm for 15 min. Finally, 7.58 parts by weight of antioxidant nano-dispersion was added and stirred at 500 rpm for 30 min to obtain an aqueous phase wetting solution.

[0086] In S5, the film-forming surface of the pre-wetted support layer is in contact with the first organic phase reaction liquid for 12 seconds, and after the first organic phase reaction liquid is poured off, it is allowed to drain naturally for 15 seconds; then it is in contact with the second organic phase reaction liquid for 50 seconds, and after the second organic phase reaction liquid is poured off, it is allowed to drain naturally for 30 seconds; the heat treatment temperature is 70°C, the heat treatment time is 5 minutes, and the water washing method is the same as in Example 1, thus obtaining a seawater desalination reverse osmosis membrane with antioxidant properties.

[0087] Example 3

[0088] This embodiment discloses a seawater desalination reverse osmosis membrane with antioxidant properties. The difference from Embodiment 1 is that the antioxidant nanocomponent is formed by titanium dioxide nanonuclei, dopamine and m-phenylenediamine. At the same time, the casting solution of the porous support layer and the two-stage coagulation treatment parameters are adaptively adjusted. The remaining raw material composition and preparation steps are consistent with Embodiment 1.

[0089] In this embodiment, the porous support layer casting solution comprises the following components by weight: 17.0 parts polysulfone, 1.5 parts polyvinylpyrrolidone, 5.0 parts lithium chloride, and 76.5 parts N,N-dimethylformamide.

[0090] Among them, the polysulfone is bisphenol A type polysulfone with a weight average molecular weight of 65,000 and a glass transition temperature of 185℃; the K value of polyvinylpyrrolidone is 30; the lithium chloride is anhydrous lithium chloride with a purity of 99.0%; and the purity of N,N-dimethylformamide is 99.5%.

[0091] The antioxidant nano-dispersion comprises the following components by weight: 1.00 parts titanium dioxide nanoparticles, 0.16 parts dopamine, 0.08 parts m-phenylenediamine, and 198.76 parts deionized water.

[0092] Among them, the titanium dioxide nanoparticles are anatase titanium dioxide nanoparticles with an original average particle size of 18 nm, a particle size distribution D90 of 42 nm, and a purity of 99.0%; the dopamine purity is 98.0%; the m-phenylenediamine purity is 99.0%; and the deionized water conductivity is 0.8 μS / cm.

[0093] The aqueous phase wetting solution comprises the following components by weight: 2.2 parts m-phenylenediamine, 1.4 parts triethylamine, 0.030 parts sodium dodecyl sulfate, 8.06 parts antioxidant nano-dispersion, and 88.31 parts deionized water. The antioxidant nano-components constitute 0.05% of the aqueous phase wetting solution by mass.

[0094] The first organic phase reaction solution comprises, by weight, the following components: 0.015 parts of pyromellitic methyl chloride and 99.985 parts of n-hexane.

[0095] The second organic phase reaction solution comprises the following components by weight: 0.100 parts of trimesoyl chloride and 99.900 parts of n-hexane.

[0096] The purity of pyromellitic chloride is 98.0%; the purity of n-hexane is 99.0%; and the water content is not higher than 0.02 wt%. The mass concentration of pyromellitic chloride in the first organic phase reaction solution is 15.0% of the mass concentration of pyromellitic chloride in the second organic phase reaction solution.

[0097] In the preparation process, 76.5 parts by weight of N,N-dimethylformamide were added to a dry reaction vessel equipped with mechanical stirring in S1. 5.0 parts by weight of anhydrous lithium chloride were added at 25°C and stirred at 300 rpm for 30 min to completely dissolve the anhydrous lithium chloride. Then, 1.5 parts by weight of polyvinylpyrrolidone were added and stirred at 400 rpm for 40 min. Next, 17.0 parts by weight of polysulfone were added in 4 portions, and stirred at 500 rpm for 20 min after each addition. After all the polysulfone was added, the temperature was raised to 60°C and stirred at 500 rpm for 6 h to obtain the support layer casting solution.

[0098] The casting solution for the support layer was allowed to stand at 60℃ for 4 hours to degas, then cooled to 25℃ and coated onto the surface of a polyester nonwoven fabric substrate using a doctor blade with a spacing of 180 μm and a coating speed of 8 cm / s. After coating, it was left to stand in air at 25℃ and 55% relative humidity for 22 seconds. The first coagulation bath consisted of an aqueous solution containing 12.0 wt% N,N-dimethylformamide, with a treatment time of 50 seconds and a coagulation temperature of 25℃. The second coagulation bath consisted of deionized water, with a treatment time of 15 minutes and a coagulation temperature of 25℃. After treatment, the membrane was immersed in fresh deionized water for 12 hours, with the deionized water being replaced every 3 hours, resulting in a porous support layer.

[0099] In step S2, 198.76 parts by weight of deionized water were added to a reaction vessel, and 1.00 parts by weight of titanium dioxide nanoparticles were added at 25°C. The mixture was stirred at 600 rpm for 20 min, followed by ultrasonic dispersion for 15 min at an ultrasonic power of 300 W. During the ultrasonic process, the temperature of the dispersion was controlled to not exceed 30°C to obtain a preliminary titanium dioxide dispersion. 0.16 parts by weight of dopamine were added to the preliminary titanium dioxide dispersion, and the mixture was stirred at 500 rpm for 20 min. Then, 0.08 parts by weight of m-phenylenediamine were added, and the mixture was stirred at 500 rpm for another 20 min. The pH of the system was adjusted to 8.5 using a 0.1 mol / L sodium hydroxide aqueous solution, and the mixture was stirred at 500 rpm for 4 h at 25°C. After the reaction was completed, the mixture was filtered through a 0.22 μm polyethersulfone membrane, and the filtrate was collected to obtain an antioxidant nano-dispersion with a dopamine-m-phenylenediamine organic coating on the surface.

[0100] In step S3, 88.31 parts by weight of deionized water were added to a clean container, and 2.2 parts by weight of m-phenylenediamine were added at 25°C. The mixture was stirred at 400 rpm for 20 min to completely dissolve the m-phenylenediamine. Then, 1.4 parts by weight of triethylamine were added and stirred at 400 rpm for 10 min. Next, 0.030 parts by weight of sodium dodecyl sulfate were added and stirred at 400 rpm for 15 min. Finally, 8.06 parts by weight of antioxidant nano-dispersion were added and stirred at 500 rpm for 30 min to obtain an aqueous phase wetting solution.

[0101] In S5, the film-forming surface of the pre-wetted support layer is in contact with the first organic phase reaction liquid for 8 seconds, and after the first organic phase reaction liquid is poured off, it is allowed to drain naturally for 15 seconds; then it is in contact with the second organic phase reaction liquid for 40 seconds, and after the second organic phase reaction liquid is poured off, it is allowed to drain naturally for 30 seconds; the heat treatment temperature is 65°C, the heat treatment time is 6 minutes, and the water washing method is the same as in Example 1, thus obtaining a seawater desalination reverse osmosis membrane with antioxidant properties.

[0102] Comparative Example 1 This comparative example discloses a seawater desalination reverse osmosis membrane. The difference from Example 1 is that no antioxidant nano-dispersion is added to the aqueous phase wetting solution, and an equal amount of deionized water is used to replace the antioxidant nano-dispersion. The remaining raw material composition and preparation steps are consistent with those of Example 1.

[0103] In the seawater desalination reverse osmosis membrane obtained in this comparative example, polyamide separation structures can still be formed on the surface of the selective separation layer, but the distribution of antioxidant nano-components in the selective separation layer was not detected.

[0104] Comparative Example 2 This comparative example discloses a seawater desalination reverse osmosis membrane. The difference from Example 1 is that cerium dioxide nanoparticles that have not been coated with gallic acid and polyethyleneimine are used to replace the antioxidant nanoparticles in the antioxidant nanodispersion. The remaining raw material composition and preparation steps are consistent with those of Example 1.

[0105] In the seawater desalination reverse osmosis membrane obtained in this comparative example, local particle aggregation was observed on the outer surface of the selective separation layer. Statistical analysis of at least five different locations using 10μm×10μm electron microscopy revealed that the number of particle aggregates with a diameter greater than 500nm was 9, 12, 11, 10, and 13, respectively, with an average of 11.

[0106] Comparative Example 3 This comparative example discloses a seawater desalination reverse osmosis membrane. The difference from Example 1 is that instead of using the method of sequential contact between the first organic phase reaction liquid and the second organic phase reaction liquid, it uses a single organic phase reaction liquid for interfacial polymerization. The remaining raw material composition and preparation steps are consistent with those of Example 1.

[0107] In this comparative example, the single organic phase reaction solution, by weight, includes the following components: 0.120 parts of trimesoyl chloride and 99.880 parts of n-hexane.

[0108] The purity of pyromellitic methyl chloride is 98.0%; the purity of n-hexane is 99.0%; and the water content is no more than 0.02 wt%.

[0109] The specific steps for S5 are as follows: The film-forming surface of the pre-wetted support layer is brought into contact with the single organic phase reaction solution for 55 seconds. After contact, the single organic phase reaction solution is poured off, and the film surface is allowed to drain naturally for 30 seconds.

[0110] The membrane that has completed the interfacial polymerization reaction was placed in a hot air drying oven for heat treatment at 70℃ for 5 minutes. After heat treatment, the membrane was washed in 25℃ deionized water for 10 minutes, and then immersed in fresh deionized water for 30 minutes to obtain the seawater desalination reverse osmosis membrane.

[0111] In the seawater desalination reverse osmosis membrane obtained in this comparative example, the selective separation layer thickness was 250 nm. The area starting from the outer surface of the selective separation layer and accounting for 60% of the selective separation layer thickness was defined as the outer surface region and the near-surface region. The number of antioxidant nanoparticles in this region accounted for 57% of the total number of antioxidant nanoparticles in the selective separation layer. Surface electron microscopy revealed small blocky aggregate structures formed by the rapid sealing of particles in local areas.

[0112] Comparative Example 4 This comparative example discloses a seawater desalination reverse osmosis membrane. The difference from Example 1 is that the first-stage coagulation bath containing N,N-dimethylformamide is not used in the preparation of the porous support layer. Instead, deionized water is used directly for single-stage coagulation treatment. The composition of other raw materials and preparation steps are consistent with those of Example 1.

[0113] In this comparative example, the porous support layer casting solution, by weight, includes the following components: 18.0 parts polysulfone, 1.2 parts polyvinylpyrrolidone, 4.0 parts lithium chloride, and 76.8 parts N,N-dimethylformamide.

[0114] Among them, the polysulfone is bisphenol A type polysulfone with a weight average molecular weight of 65,000 and a glass transition temperature of 185℃; the K value of polyvinylpyrrolidone is 30; the lithium chloride is anhydrous lithium chloride with a purity of 99.0%; and the purity of N,N-dimethylformamide is 99.5%.

[0115] The specific steps in S1 are as follows: 76.8 parts by weight of N,N-dimethylformamide were added to a dry reaction vessel equipped with mechanical stirring. 4.0 parts by weight of anhydrous lithium chloride were added at 25°C. The mixture was stirred at 300 rpm for 30 min to completely dissolve the anhydrous lithium chloride, thus obtaining the first mixture.

[0116] Add 1.2 parts by weight of polyvinylpyrrolidone to the first mixture and stir at 400 rpm for 40 min to uniformly disperse and dissolve the polyvinylpyrrolidone, thus obtaining the second mixture.

[0117] 18.0 parts by weight of polysulfone were added to the second mixture in four portions, with 4.5 parts by weight added each time. After each addition, the mixture was stirred at 500 rpm for 20 min. After all the polysulfone was added, the temperature was raised to 60°C and stirred at 500 rpm for 6 h to obtain a uniform and transparent support layer casting solution.

[0118] The support layer casting solution was allowed to stand at 60℃ for 4 hours to degas, and then cooled to 25℃. A polyester nonwoven fabric substrate was fixed to a glass plate, and the support layer casting solution was applied to the surface of the substrate using a doctor blade with a blade spacing of 180 μm and a coating speed of 8 cm / s. After coating, the substrate coated with the support layer casting solution was allowed to remain in air at 25℃ and 55% relative humidity for 18 seconds.

[0119] After the air residence period, the substrate coated with the support layer casting solution was directly immersed in a deionized water coagulation bath at 25°C for 15 minutes. After treatment, the membrane was soaked in fresh deionized water for 12 hours, with the deionized water being changed every 3 hours, to obtain a porous support layer.

[0120] The porous support layer obtained in this comparative example showed an indistinct fine transition region near the selective separation layer, and the uniformity of the surface pore size distribution was reduced. Cross-sectional electron microscopy revealed that the maximum depth of the antioxidant nanoparticles penetrating the porous support layer was 2.8 μm, higher than the 1.4 μm in Example 1. Local thickness fluctuations were observed in the obtained selective separation layer.

[0121] Performance testing To verify the antioxidant stability, separation performance retention, and antioxidant nanocomposition distribution of the seawater desalination reverse osmosis membranes obtained in each embodiment and comparative example, the membrane samples obtained in Example 1 and Comparative Examples 1-4 were subjected to the following tests. Before testing, each membrane sample was soaked in deionized water for 12 hours and pre-pressurized under the test pressure for 30 minutes. Data were recorded after the water flux stabilized.

[0122] 1. Initial desalination performance test The membrane sample was placed in a flat-sheet membrane test cell, with an effective membrane area of ​​28.0 cm². 2 The test solution was a 3.2% sodium chloride aqueous solution, the test temperature was 25℃, the operating pressure was 5.5MPa, and the cross-flow rate was 1.0L / min. After pre-pressuring the membrane sample for 30 min, the permeate was collected within 30 min, and the water flux was calculated. The conductivity of the feed water and permeate was measured separately, and the results were calculated according to the formula. Calculate the salt rejection rate, where R is the salt rejection rate. To achieve the desired liquid salt concentration, This represents the influent salt concentration. Three membranes were tested for each sample, and the average value was taken.

[0123] 2. Test on the retention rate of desalination performance after oxidation treatment The membrane sample was placed in an aqueous solution of sodium hypochlorite with an effective chlorine concentration of 1000 mg / L. The pH of the solution was adjusted to 7.0, the treatment temperature was 25℃, and the treatment time was 2 h. After treatment, the membrane sample was thoroughly rinsed with deionized water for 30 min, and then soaked in deionized water for 2 h. Subsequently, the water flux and salt rejection rate were retested according to the initial desalination performance testing method. The water flux retention rate was calculated by dividing the water flux after oxidation treatment by the initial water flux, and the salt rejection rate retention rate was calculated by dividing the salt rejection rate after oxidation treatment by the initial salt rejection rate.

[0124] 3. Detection of the distribution and aggregation state of antioxidant nanocomponents After freeze-drying, the membrane samples underwent cross-sectional brittle fracture treatment. Scanning electron microscopy was used to observe the membrane cross-section and surface morphology, and energy dispersive spectroscopy (EDS) was used to detect the distribution of corresponding elements of the antioxidant nanoparticles in the selective separation layer and porous support layer. For Example 1 and the comparative example containing inorganic oxide nanoparticles, the maximum depth of the antioxidant nanoparticles penetrating into the porous support layer was counted in at least five cross-sectional fields of view, and the number of particle aggregates with a diameter greater than 500 nm was counted in at least five 10 μm × 10 μm observation areas on the surface. The proportion of antioxidant nanoparticles in the outer surface region and near-surface region was expressed as the ratio of the number of antioxidant nanoparticles in these regions to the total number of antioxidant nanoparticles in the selective separation layer.

[0125] 4. Continuous operation flux attenuation detection Membrane samples were loaded into a flat-sheet membrane test cell, and a 3.2% (w / w) sodium chloride aqueous solution was used as the test solution. The membrane was continuously run for 24 hours at 25°C and 5.5 MPa. Water flux was recorded at 0.5 hours and 24 hours, and the continuous operation flux retention rate was calculated by dividing the 24-hour flux by the 0.5-hour flux. This assay was used to evaluate the effects of selective separation layer integrity, porous support layer permeable channel stability, and nano-component aggregation on flux decay.

[0126] The test results are shown in Tables 1 and 2 below.

[0127] Table 1

[0128] Table 2

[0129] The test results show that the water flux in Example 1 was 28.6 L·m⁻² in the initial state. -2 ·h -1 The salt rejection rate was 99.42%, indicating that the polyamide selective separation layer maintained good density after the introduction of the antioxidant nanocomponents, and the porous support layer did not experience significant clogging due to the addition of the nanocomponents. After treatment with 1000 mg / L available chlorine for 2 hours, the water flux retention rate in Example 1 was 97.2%, and the salt rejection rate was 99.76%, indicating that the antioxidant nanocomponents formed by the cerium dioxide nanocores and the gallic acid-polyethyleneimine organic coating layer can mitigate the damage of oxidizing media to the polyamide separation matrix.

[0130] Comparative Example 1, without the addition of antioxidant nano-components, had an initial salt rejection rate of 99.28%, but after oxidation treatment, the salt rejection rate decreased to 96.41%, and the water flux increased to 35.6 L·m⁻¹. -2 ·h -1The water flux retention rate reached 122.3%. This result indicates that when the polyamide selective separation layer is subjected to oxidizing media, it is prone to problems such as decreased selectivity and increased non-selective permeability, manifested as a significant decrease in salt rejection rate and an abnormal increase in water flux.

[0131] Comparative Example 2 used uncoated cerium dioxide nanoparticles. Although it still exhibited some antioxidant properties, the proportion of surface and near-surface nanoparticle components was 63%, lower than the 78% in Example 1. The number of large particle agglomerates increased to 11 per 10 μm × 10 μm, and both the initial salt rejection rate and 24-hour flux retention rate were lower than in Example 1. These results indicate that the gallic acid-polyethyleneimine organic coating layer helps improve the dispersion stability of cerium dioxide nanoparticles in aqueous wetting solutions and polyamide separation matrices, and also helps reduce local defects caused by large-sized agglomerates.

[0132] Comparative Example 3 used a single organic phase reaction solution for interfacial polymerization. The proportion of antioxidant nanoparticles in the surface and near-surface layers decreased to 57%, lower than 78% in Example 1; the salt rejection rate after oxidation was 98.02%, lower than 99.18% in Example 1. These results indicate that the combination of low-concentration first organic phase pre-fixation and higher-concentration second organic phase densification is beneficial for the formation of a more concentrated distribution of antioxidant nanoparticles in the outer surface and near-surface regions of the selective separation layer, and helps maintain the separation performance after oxidation treatment.

[0133] In Comparative Example 4, after eliminating the two-stage coagulation treatment, the maximum depth of the antioxidant nanocomponents penetrating into the porous support layer increased to 2.8 μm, higher than the 1.4 μm in Example 1; the 24-hour flux retention rate decreased to 84.9%. These results indicate that the surface bearing interface formed by the single-stage water coagulation treatment lacks sufficient stability, easily leading to the aqueous wetting solution penetrating deeper into the support layer, thus affecting the uniformity of the selective separation layer film formation and the stability of continuous operation.

[0134] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.

Claims

1. A seawater desalination reverse osmosis membrane with antioxidant properties, characterized in that, Includes a porous support layer and a selective separation layer formed on one side surface of the porous support layer; The selective separation layer includes a polyamide separation matrix and antioxidant nanocomponents dispersed in the polyamide separation matrix. The antioxidant nanocomponents include inorganic oxide nanocores and phenolic hydroxyl-amine organic coating layers coated on the surface of the inorganic oxide nanocores. The antioxidant nanoparticles are distributed in the outer surface region and near-surface region of the selective separation layer. The outer surface region and near-surface region are areas that start from the outer surface of the selective separation layer and occupy 60% of the thickness of the selective separation layer. The amount of antioxidant nanoparticles in this region accounts for 65% to 90% of the total amount of antioxidant nanoparticles in the selective separation layer. The outer surface of the selective separation layer is covered with a continuously covered nanoparticle-like rough structure, which is composed of multiple adjacent spherical or near-spherical protrusions, with an average particle size of 30 nm to 180 nm. The porous support layer has an asymmetric pore structure, and along the direction away from the selective separation layer, it sequentially includes a dense transition region close to the selective separation layer, a finger-shaped pore region located below the dense transition region, and a sponge-like pore region located below the finger-shaped pore region. The thickness of the dense transition region is 0.3 μm to 3.0 μm, and fine pores with a diameter of less than 0.5 μm are distributed within the dense transition region.

2. The seawater desalination reverse osmosis membrane with antioxidant properties according to claim 1, characterized in that, The inorganic oxide nanonucleus is selected from one of cerium dioxide nanoparticles, manganese dioxide nanoparticles, zinc oxide nanoparticles, and titanium oxide nanoparticles; the phenolic hydroxyl-amine organic coating layer is formed by a phenolic hydroxyl-containing compound and an amine-containing compound, wherein the phenolic hydroxyl-containing compound is selected from one of gallic acid, tannic acid, and dopamine, and the amine-containing compound is selected from one of m-phenylenediamine, polyethyleneimine, and triethylenetetramine.

3. The seawater desalination reverse osmosis membrane with antioxidant properties according to claim 1, characterized in that, The average particle size of the antioxidant nanocomponent is 5 nm to 80 nm, and the mass content of the antioxidant nanocomponent in the selective separation layer is 0.05% to 2.0%; on the outer surface of the selective separation layer, the number of antioxidant nanocomponent agglomerates with a diameter greater than 500 nm in any 10 μm × 10 μm observation area does not exceed 8.

4. The seawater desalination reverse osmosis membrane with antioxidant properties according to claim 1, characterized in that, The spherical or near-spherical protrusions form nanoscale recessed gaps, the width of which is 10nm to 120nm; the thickness of the selective separation layer is 80nm to 500nm; the selective separation layer and the porous support layer form a continuous bonding interface; and the selective separation layer shows no through cracks under a 2μm scale electron microscope.

5. The seawater desalination reverse osmosis membrane with antioxidant properties according to claim 1, characterized in that, The thickness of the finger-shaped pore region accounts for 35% to 80% of the total thickness of the porous support layer, the thickness of the dense transition region accounts for 1% to 10% of the total thickness of the porous support layer, and the sponge-like pore region includes irregularly connected pores with a pore size of 0.2 μm to 5 μm.

6. The seawater desalination reverse osmosis membrane with antioxidant properties according to claim 1, characterized in that, The finger-shaped pore region includes multiple elongated pores extending along the film thickness direction. The length of each elongated pore is 5μm to 45μm, and the width is 0.5μm to 6μm. Adjacent elongated pores are separated by porous framework walls, which are distributed with interconnecting pores with a diameter of 0.05μm to 1.5μm. The maximum depth to which the antioxidant nanocomponent enters the porous support layer does not exceed 1.5 times the thickness of the dense transition region.

7. A method for preparing a seawater desalination reverse osmosis membrane with antioxidant properties as described in any one of claims 1-6, characterized in that, Includes the following steps: S1, Preparation of a porous support layer: The film-forming polymer, a dense transition modifier, a pore-forming agent and an organic solvent are mixed to obtain a support layer casting solution. The support layer casting solution is coated on the surface of the substrate. After air retention and two-stage coagulation treatment, a porous support layer with a dense transition region, a finger-like pore region and a sponge-like pore region is obtained. S2, Preparation of antioxidant nano-dispersion: Inorganic oxide nanoparticles, phenolic hydroxyl compounds and amine compounds are dispersed in water and treated under pH conditions of 7.5 to 9.5 to obtain an antioxidant nano-dispersion with a phenolic hydroxyl-amine organic coating layer on the surface; S3, Preparation of aqueous phase wetting solution: mix m-phenylenediamine, acid absorbent, surface wetting regulator and antioxidant nano-dispersion obtained in step S2 to obtain aqueous phase wetting solution; S4, the porous support layer obtained in step S1 is brought into contact with the aqueous wetting liquid obtained in step S3 to remove excess liquid from the surface of the porous support layer, thereby obtaining a pre-wetting support layer with surface-loaded antioxidant nano-components and m-phenylenediamine. S5, the pre-wetting support layer obtained in step S4 is brought into contact with the first organic phase reaction liquid and the second organic phase reaction liquid in sequence. After heat treatment and water washing, a seawater desalination reverse osmosis membrane with antioxidant properties is obtained. The mass concentration of pyromellitic chloride in the first organic phase reaction solution is lower than that in the second organic phase reaction solution.

8. The preparation method according to claim 7, characterized in that, In step S1, the film-forming polymer is selected from polysulfone, polyethersulfone, and polyvinylidene fluoride; the dense transition modifier is selected from polyvinylpyrrolidone, polyethylene glycol, and sulfonated polyethersulfone; and the pore-forming agent is selected from polyethylene glycol, lithium chloride, and glycerol. In the casting solution of the support layer, the mass content of the film-forming polymer is 14%–22%, the mass content of the dense transition modifier is 0.3%–2.5%, the mass content of the pore-forming agent is 2%–10%, and the mass content of the organic solvent is 65.5%–83.7%. The air residence time is 8s to 35s; the two-stage coagulation process includes a first stage coagulation process and a second stage coagulation process. The first stage coagulation process uses an aqueous solution containing 5% to 20% organic solvent and the processing time is 10s to 80s. The second stage coagulation process uses water and the processing time is 5min to 30min.

9. The preparation method according to claim 7, characterized in that, In step S2, the mass ratio of the inorganic oxide nanoparticles, the phenolic hydroxyl compound, and the amine compound is 1:0.05-0.40:0.03-0.30; In step S3, the aqueous phase wetting solution comprises the following components in the indicated mass percentages: m-phenylenediamine 1.5%–4.0%, acid absorbent 0.5%–3.0%, surface wetting modifier 0.005%–0.08%, antioxidant nano-components 0.005%–0.20%, and the balance being water; The acid absorbent is selected from one of triethylamine, camphor sulfonate, and sodium bicarbonate, and the surface wetting modifier is selected from one of sodium dodecyl sulfate, polyether-modified siloxane, and fatty alcohol polyoxyethylene ether.

10. The preparation method according to claim 7, characterized in that, In step S5, the first organic phase reaction solution includes pyromellitic trimethylol chloride and an organic solvent with a mass concentration of 0.005% to 0.05%, and the contact time between the pre-wetting support layer and the first organic phase reaction solution is 3s to 20s. The second organic phase reaction solution includes 0.06% to 0.25% trimesoyl chloride and an organic solvent, and the contact time between the pre-wetted support layer and the second organic phase reaction solution is 15s to 90s. The heat treatment temperature is 50℃~90℃, and the time is 2min~10min; The mass concentration of pyromellitic chloride in the first organic phase reaction solution is 5% to 40% of the mass concentration of pyromellitic chloride in the second organic phase reaction solution.